KARAKTERISTIK SENSORIS PERMEN â€œPANDANUS HARD CANDYâ€ DENGAN BERBAGAI KONSENTRASI EKSTRAK DAUN PANDAN - Iswandi, Donni; Murtado, AD; Domonita, Heni (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2013)
This study aims to determine the range of concentrations of pandan leaf extract against candy "pandanus hard candy". This research has been carried out in the Laboratory of the Faculty of Agriculture, University of Muhammadiyah Palembang October 2012 to April 2013. This research method using a randomized block design arranged in a non-factorial consisted of five treatments extraction repeated five times with each treatment is D1 (pandan extract 5 ml, glucose syrup 350g, 190 g sugar, and margarine 5 g), D2 (pandan extract 10 ml, glucose syrup 350g, 190 g sugar, and margarine 5 g), D3 (15 ml pandan extract, glucose syrup 350g, 190 g sugar, and margarine 5 g), D4 (pandan extract 20 ml , glucose syrup 350g, 190 g sugar, and margarine 5 g), and D5 treatment (25 ml pandan extract, glucose syrup 350g, 190 g sugar, and margarine 5 g). Parameters observed in the study consisted of chemical analysis covering the water content and vitamin C, while sensory consists of color and flavor. The results showed that the formulation very significant effect on the moisture content, vitamin C. Organoleptic assessment showed that the formulation significantly affect the flavor, color, "Pandanus Hard Candy". From the results of the study concluded that D5 treatment produces candy "Pandanus Hard Candy" with the best water content (2,169%), vitamin C (4,359 mg/100g), color (4,00), aroma (3,66) and the sense of (3,76) with the criteria somewhat favored until as well as preferred by the panelists.